[Rezension von: Vinzent, Markus, 1959-, Writing the history of early Christianity] - Ramelli, Ilaria 1973-; Vinzent, Markus 1959- (2021)
In line with Vinzent’s interesting ‘retrospective’ approach, the preface is a postscript. The introduction takes over Paul Veyne’s distinction between forward narration and retrospective historical interpretation, and Tertullian’s motto ex futuro praesens, ex praesenti praeteritum deputatur (Apol. 20.5). ‘Retrospection’ reacts to reception history and builds on new historicism, but the RAC is rightly recognized as ‘the only comprehensive encyclopaedia worldwide covering all the major aspects of the transformation of late antique culture’ (p. 85).The first case study, the Epitaph of Abercius, ‘the queen of Christian funerary inscriptions’ (de Rossi), has been reconstructed by integrating the late Vita Abercii, which knows events of the second century, but betrays a chronological inconsistency (p. 111). The latter characteristic is typical, I note, of other early Christian documents, such as the Seneca-Paul correspondence (as I argued in ‘A Pseudepigraphon inside a Pseudepigraphon?’ JSP 23 [2014], pp. 259-89), Acts of Mari, and Doctrina Addai. The Vita uses a lost letter by Marcus Aurelius (p. 112). Similarly, the Abgar-Tiberius letters probably constituted the historical nugget of the Abgar legend. The Epitaph is now deemed ‘Christian’ (p. 95), although its language is ambiguous: Allen Brent points to its ‘pagan’ background. Paul McKechnie, Christianizing Asia Minor (Cambridge, 2019), ch. 6, traditionally identifies the inscription’s Abercius with Eusebius’ Avircius Marcellus and interprets the inscription in light of Montanism.
Keywords: Rezension